Nitrogen-Induced Changes in Soil Environmental Factors Are More Important Than Nitrification and Denitrification Gene Abundance in Regulating N2O Emissions in Subtropical Forest Soils - Qiu, Qingyan; Mgelwa, Abubakari Said; Jin, Shaofei; Hu, Yalin (Frontiers in Plant Science, 2022)
Subtropical regions are currently experiencing a dramatic increase in nitrogen (N) deposition; however, the contributions of nitrification and denitrification processes to soil N2O emissions and the underlying mechanisms under increasing N deposition remain unclear. Therefore, a 15N-tracing laboratory experiment with four N application rates (0, 12.5, 25, and 50 μg 15N g–1 soil) was conducted to investigate the response of nitrification- and denitrification-derived N2O to N additions in an evergreen broad-leaved forest (BF) and a Pinus forest (PF) in the Wuyi Mountains in southeastern China. Moreover, the abundance of functional genes related to nitrification (amoA), denitrification (nirK, nirS, and nosZ), and soil properties were measured to clarify the underlying mechanisms. Results showed that nitrification-derived N2O emissions were generally decreased with increasing N input. However, denitrification-derived N2O emissions were a non-linear response to N additions, with maximum N2O emissions at the middle N application rate. Denitrification-derived N2O was the dominant pathway of N2O production, accounting for 64 to 100% of the total N2O fluxes. Soil NH4+-N content and pH were the predominant factors in regulating nitrification-derived N2O emissions in BF and PF, respectively. Soil pH and the nirS abundance contributed the most to the variations of denitrification-derived N2O emissions in BF and PF, respectively. Our results suggest that N application has the potential to increase the contribution of denitrification to N2O production in subtropical forest soils. Changes in soil chemical properties induced by N addition are more important than the abundance of nitrification and denitrification functional genes in regulating soil nitrification- and denitrification-derived N2O emissions.